Electrochemical Sensor Based on Three-Dimensional Nitrogen-Doped Nanostructured Porous Carbon from Edible Ulva lactuca L with a Potentially Wide Application - Qin, Jianhua; Zuo, Ying; Yu, Haiyu; Yu, Jinzhi; Chen, Xinyue; Zhang, Junling; Lv, Jubo; Xu, Hui; Gao, Shanmin; Hou, Faju; Zhong, Linlin (International journal of electrochemical science, 2020)
A simple method consisting of a one-step carbonization under a N2 atmosphere without an activation agent is used for preparing three-dimensional nitrogen-doped nanostructured porous carbons (3D-NNPCs) from edible Ulva lactuca L. It has been proposed for environmentally friendly and inexpensive electrochemical sensing. The prepared 3D-NNPCs have a high specific surface area of 1683.54 m2 g-1, a large pore volume of 1.09 cm3 g-1, a hierarchical porous structure and a high density of defective sites, all of which are beneficial for electrocatalysis. Using a 3D-NNPC-modified glassy carbon electrode (3D-NNPC/GCE), ascorbic acid (AA) is first chosen as a model to study the electrocatalytic performance. The electrode exhibits a greatly decreased overpotential (-0.015 V vs. Ag/AgCl), a lower limit of detection with a sensitivity of 0.055 μA·μM-1·cm-2, a wide linear range spanning 4 orders of magnitude (1 μM-10 mM), and a good selectivity. The above results show that the electrode has promise for practical application in food analysis. In addition, its potentially wide application is examined by using voltammetric determination for other biomolecules.